Constituting link working through choice and care: An ethnographic account of front‐line social prescribing. Issue 2 (25th October 2022) - Griffith, Bethan; Pollard, Tessa; Gibson, Kate; Jeffries, Jayne; Moffatt, Suzanne
Abstract: Link worker social prescribing has become a prominent part of NHS England's personalisation agenda. However, approaches to social prescribing vary, with multiple discourses emerging about the potential of social prescribing and different interpretations of personalisation. The transformational promise of social prescribing is the subject of ongoing debate, whilst the factors that shape the nature of front‐line link working practices remain unclear. Based on 11 months of in‐depth ethnographic research with link workers delivering social prescribing, we show how link workers' practices were shaped by the context of the intervention and how individual link workers navigated varied understandings of social prescribing. Following the work of Mol, we show how link workers drew differentially on the interacting logics of choice and care and trace a multiplicity in front‐line link working practices within a single intervention. However, over time, it appeared that a logic of choice was becoming increasingly dominant, making it harder to deliver practices that aligned with a logic of care. We conclude that interpreting personalisation through a logic of choice could potentially undermine link working practices that privilege care whilst obscuring the need for wider investment in health care systems and the social determinants of health.